Kinetic study of reverse water-gas shift chemical looping on La-based perovskite - Pomiro, Federico José; Fouga, Gastón Galo; Bohe, Ana Ester; Gayone, Julio Esteban; de Micco, Georgina (Elsevier, 2024)
Fil: Pomiro, Federico José. Comisión Nacional de Energía Atómica. Gerencia Complejo Tecnológico Pilcaniyeu; Argentina. Universidad Nacional de San Martín. Instituto Sabato; Argentina